Combined Operation of CABG, and Rt. Ex. Ileofemoral, Lt. Femoropopliteal Bypass: a case report - Rahman, Md. Lutfar; Badruzzaman, Md.; Chowdhury, Md. Masumul Gani (KYAMC Journal, 2013)
It is very much problematic to plan the overall therapeutic strategy in patients with coronary artery diseases (CAD) and peripheral arterial diseases (PAD) affecting several arterial segment at the same time. The great saphenous vein (GSV) is usually used as a gold standard conduit. The symptom of the CAD and PAD vary with the site of involvement. Some sorts of the symptom of CAD may be obscured in patient with both CAD and PAD due to lack of ambulation for lower limb claudication, rest pain, ulceration and gangreen. To give maximum benefit to this patient, both the CAD and PAD should be dealt simultaneously or in the same settings. In our perspective if possible and adequate facilities is available the both operations better to be done on the same table. Because it has a better compliance to the patient both for financial savings and avoidance of harassment of 2nd. operation. Our present patient who was followed for 2 months has an excellent postoperative results with disappearance of rest pain and claudication. KYAMC Journal Vol. 3, No.-2, January 2013, Page 312-314 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15175